Minority and low-SES families' experiences during the early phases of the COVID-19 pandemic crisis: A qualitative study. (September 2022) - Perrigo, Judith L.; Samek, Anya; Hurlburt, Michael
Highlights: Although the COVID-19 pandemic is unique, collective crises (times of acute difficultly) are common. Initial responses to the pandemic crises offers lessons that can be applied for future collective crises. Vulnerable populations (low-SES and minorities) are particularly important because they have less resources to buffer against potential hardships. Crisis-oriented resources can help families maintain their sense of control over their lives during early phases of a collective crisis. Long-term supports are also needed to buffer against COVID-19-related negative impacts (social inequities and disparities) Abstract: Objectives: To explore minority and low-SES families' general experiences with the stay-at-home mandate initiated by the COVID-19 pandemic crisis. Methods: Semi-structured qualitative interviews ( n = 31) were conducted in May 2020 – six to nine weeks after the stay-at-home mandate was initiated in Chicago Heights, Illinois. Participants were randomly selected from the parent Chicago Heights Early Childhood Center (CHECC) study ( N = 2, 185) . Thematic content analysis of transcribed semi-structured interviews were employed. Results: During the early phases of the COVID-19 pandemic crisis, ethnic minority and low-SES families were generally comfortable in their homes, but both children and their parents experienced poor wellbeing, such as elevated stress. Families reportedly avoided social resources, despite low-SES. Upon reflection, parents expressed that the pandemic had changed them and, in some ways, the changes were positive. Conclusion: Readily available crisis-oriented resources, for both children and parents, are needed to help families maintain or rebuild their sense of control over their lives during the early phases of a collective crisis (e.g., pandemic). Although early observations help to contextual families' initial experiences, examining long-term trends can inform meaningful policies and practices that both support how low-SES families buffer against COVID-19-related negative impacts and mitigate ethnic and SES inequities and disparities.